Does Exporting Raise Productivity? Evidence from Korean Microdata - Sanghoon Ahn (Asian Development Bank Institute (ADBI), 2005)
Does competition enhance productivity growth of a developing economy? Is global competition conducive to economic development? Especially, does competition with more advanced producers in the global market promote productivity growth of domestic producers in a developing country? If the answer is a conditional yes, what makes global competition conducive to productivity growth and economic development? Many researchers have been working to find a better answer to these, perhaps quite controversial, questions. The aim of this paper is to review recent empirical findings related to these questions, which have strong policy implications, and to offer some new evidence from Korean micro-data. The paper explores a plausible channel through which exporting could have made both a substantial and a persistent contribution to export-oriented economic growth in Korea and by extension other East Asian NIEs: namely, the spillovers (or externalities) of learning-by-exporting. Plant-level data for Korean manufacturing show that more export-intensive industries tend to have a higher productivity level. In addition, a substantial part of the variance in plant-level productivity is explained by the variance in industry-level export intensity. These findings are consistent with the hypothesis that there exist spillovers of learning-by-exporting at least in some industries. As with the existence of the more usual intra-industry R&D spillovers, which are also demonstrated here, this raises the policy questions of how to get more benefits from such spillovers, whilst minimizing any side-effects from any policy intervention. As in the case of other types of positive externalities, in theory a market solution will lead to a sub-optimal level of externality-generating output (in this case exports), indicating that government action could improve upon the market outcome. This is the implicit logic behind the active role played by the Japanese government or by the Korean government at earlier stages of their economic development. (Needless to say, however, the existence of such externalities does not justify the abuse or misuse of government intervention in the market.) It should also be emphasized that competition in one segment of the market may not be a permanent substitute for competition in other areas. In other words, dynamic efficiency gains from competition in the export market cannot be fully realized and sustained without emerging competition in other areas of the economy. An export-oriented development strategy has been highly successful for Korea, and some other countries in East Asia, in the past, but lack of competition outside the export market, partly due to insufficient institutional development in areas such as the capital market, the labor market, and the market for corporate control, restricts the productivity gains from exporting. Perhaps this is one important lesson to be learned from the long economic stagnation in Japan and from the financial crisis in Korea and other East Asian NIEs.
hdl:11540/4173
Keywords: 330